?A STUDY ON THE FEEDING RESPONSES OF A FILTER - FEEDING CYCLOPS SP. ON VARIOUS CONCENTRATIONS OF CHLORELLA VULGARIS (Biological Sciences - PJSIR, 2003)
The feeding responses of Cyclops sp. fed on Chlorella vulgaris at various concentrations were studied. The filtration rate of Cyclops ranged from 3.0 to 6.43 ?l/h/individual. The range of food concentrations was 515 to 2039 cells/?l. The critical food concentration was 1435 cells/?l. The ingestion rate was recorded a maximum of 9971 cells/h/individual at the concentration of 771 cells/?l. This study also relates filtration rate with pH and dissolved oxygen.